Contrastive analysis of politeness strategies in refusal speech acts: A study of Sundanese and Batak language - Rossy Halimatun Rosyidah (Universitas Muhammadiyah Malang, 2025)
This research examines politeness strategies in refusal speech acts used by Sundanese andBatak speakers. The purpose of this research is to test the truth of the stereotype which statesthat Batak people tend to be loud or rude, while Sundanese people are considered smoothand polite in communicating. This research used a qualitative methodology and a contrastiveanalysis approach. A total of ten informants participated in this research, consisting of fivenative Toba Batak speakers and five native Sundanese speakers who were around fifty yearsold. Data were collected through the Discourse Completion Task (DCT). Data analysis usesMiles et al., (2014) interactive model, which involves three stages: data condensation, datapresentation, and verification. Data validity uses triangulation. The findings show that Batakand Sundanese speakers both use negative politeness strategies, while Sundanese speakersalso use positive politeness strategies. Negative politeness is used to maintain relationshipswhile respecting the rights of the interlocutor, for example by expressing regret, giving clearreasons, or emphasizing personal inability to fulfil requests and positive politeness strategiesare used to maintain harmony and show attention to the feelings of the interlocutor. Theyavoid using the bald-on-record strategy (direct rejection without further ado). These findingsshow that the stereotypes that exist in society are not true, both Batak and Sundanesespeakers prioritize respect and harmony in communication